SEJARAH DAKWAH SULTAN SYARIF ABDURRAHMAN AL-QADRI: ISLAMISASI DI PONTIANAK - Zakaria Efendi (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2021)
This article attempts to explain the history of the da'wah of Sultan Syarif Abdurrahman Al-Qadri through the Kadriah Sultanate in carrying out Islamization in Pontianak. The success of the da'wah of Sultan Syarif Abdurrahman Al-Qadri in carrying out Islamization in Pontianak is closely related to the power factor. However, there is a significant role that paved the way for the establishment of the Kadriah Sultanate to reach the peak of its existence, namely the communication factor. The figure of a wise leader allows the influence of Islam to grow rapidly. This study uses a descriptive qualitative approach, and by reviewing the literature of previous studies in order to obtain data that supports in compiling a paper on the history of the da'wah of Sultan Syarif Abdurrahman Al-Qadri in carrying out Islamization in Pontianak. The results showed that: (1) The success of Sultan Syarif Abdurrahman Al-Qadri's da'wah in carrying out Islamization in Pontianak was due to the influence of power. (2) The Sultanate became an effective da'wah media, because the Sultanate became the holder of political and economic power who had the authority to regulate policies in the area of ​​power that contributed greatly to spreading Islamic teachings (3) The acculturation approach of culture in spreading Islam among local communities became the right strategy used Sultan Syarif Abdurrahman Al-Qadri in carrying out Islamization in Pontianak. Until now, there have been many studies conducted with the object of the Kadriah Sultanate which was once the center of Islamic government in Pontianak. Among them are studies that have been carried out by Alfan Firmanto who wrote about